An Efficient Single-Frequency Yb-Doped All-Fiber MOPA Laser at 1064.3 nm - 康进 陆宝乐 齐新元 冯晓强 陈浩伟 江曼 王洋 付盼 白晋涛 (Chinese physics letters, 2016)
An efficient narrow=linewidth single-frequency （SF） Yb-doped all-fiber master oscillator power amplifier （MOPA） laser operating at 1064.3 nm is demonstrated experimentally. A ring cavity SF fiber laser is used as the seed source for the MOPA system and the Yb-doped fibers are employed as the gain medium or the saturable absorber. The SF operation is observed to be stable without mode hopping. The highest output power of 266 mW is obtained under the 400row pump power with the corresponding slope efficiency of 66.2-. The Hnewidth of the amplified output laser is approximately I kHz and its optical signal-to-noise ratio is over 45 dB.